إسهامات علماء المدرسة الإباضية في الاجتهاد الفقهي في ضوء المستويات اللغوية الأربعة = The contributions of Ibadi school scholars in jurisprudence in the light of the four linguistic levels - Bosaidi, Hamid Abdullah; Ali, Asem Shehadeh Saleh (المجلة الدولية الإلكترونية الشاملة (EIMJ), 2019)
يهدف هذا البحث الموسوم"إ إسهامات علماء المدرسة الإباضية في الاجتهاد الفقهي في ضوء المستويات اللغوية الأربعة إلى إبراز الدزر الذي قام به الفقهاء في المدرسة الإباضية في اساتباط الأحكام الفقهية من المستويات اللغوية الأربعة ، ورتبوا على ذلك حكما فقهيا سواء كان في المستوى الصوتي أو الثرفي أو النجوي أو الدلالي، مع دعم ذلك بالأمثلة من مؤلفاتهم. ***************************************************************************** This research is tagged: "Contributions Ibadi school scholars in jurisprudence jurisprudence in the light of the four linguistic levels" to highlight the role played by scholars in the Ibadi school in the development of jurisprudence provisions of the four linguistic levels and arranged a doctrinal judgment, whether in the phonetic or morphological level Or the grammar or lexical with the support of examples of their writings, and these issues the researcher believes that great efforts should appear in front of the reader so that the jurisprudence of tolerance and openness enjoyed by this school because of the multiplicity of its walks and lack of self-confinement